Distributed measurement of mode coupling in birefringent fibers with random polarization modes - Xu, Tianhua; Tang, Feng; Jing, Wencai; Zhang, Hongxia; Jia, Dagong; Zhang, Xuemin; Zhou, Ge; Zhang, Yimo (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
A scanning white light interferometer is developed to measure the distributed polarization coupling (DPC) in high birefringence polarization maintaining fibers (PMFs). Traditionally, this technique requests only one polarization mode to be excited or both polarization modes to be excited with equal intensity in the PMF. Thus, an accurate alignment of the polarization direction with the principal axis in PMF is strictly required, which is not facilely realized in practical measurement. This paper develops a method to measure the spatial distribution of polarization mode coupling with random modes excited using a white light Michelson interferometer. The influence of incident polarization extinction ratio (PER) on polarization coupling detection is evaluated theoretically and experimentally. It is also analyzed and validated in corresponding measurement that the sensitivity of the polarization coupling detection system can be improved more than 100 times with the rotation of the analyzer.
Optica Applicata, Vol. 39, 2009, nr 1, s. 77-90
Keywords: optyka; white light inteferometry; birefringent fibers; polarization coupling; polarization extinction ratio; random polarization modes